Determinación del área superficial de transferencia de calor en un intercambiador de casco y tubo aplicando el método de la LMTD y el método de la ε-NTU - Alvarez Saldaña, Sonia (2007)
The role of the heat interchangers has acquired a great importance before the need to save energy and to have ideal teams not only depending on his thermal analysis and the economic performance of the installation, but depending on other factors as the energetic utilization of the system and the availability and quantity of energy and of necessary raw materials to fulfill a certain function. The principal lens of the present work is to determine the superficial area of heat transfer in an interchanger of hull and pipe applying the method of the LMTD and the method of (it) ε-NTU by means of a program computacional interactive. The program computacional interactive developed "icct" has been codified in the language of programming Matlab 7.0. This language is nowadays a very important tool for engineers and scientific professionals. The restriction imposed in the development of the software "icct" can be modified by the user, entering to the codification of the same one. Excellent programs exist on the market of software for the design of teams of heat transfer, some of these programs are commercialized to relatively low prices. Nevertheless, for a few reasons or others, not always it is possible to acquire them. To elaborate our proper programs can be a viable alternative. Our Faculty of Chemical Engineering possesses a Laboratory of Simulation and Control of Processes, which computers Pentium allow us to test solutions to problems of heat interchangers, which beyond acquiring and using a technology, we it can create for our needs and interests of the University